World of work report 2012. Better jobs for a better economy (Geneva, 2012)
"The World of Work Report 2012 provides a comprehensive analysis of recent labour market and social trends, assesses risks of social unrest and presents employment projections for the next five years. The report emphasizes that while employment has begun to recover slowly, job quality is deteriorating and there is a growing sense of unfairness. Moreover, given the pressure on governments to rein in expenditure, policy efforts have focused on structural reforms to boost employment creation. However, if policy instruments are not carefully designed, they could exacerbate the employment situation and aggravate further equity concerns, with potentially long-lasting adverse consequences for both the economy and society."